Decompression sickness among Moroami diving fishermen in Jakarta (Medical Journal of Indonesia, 2008)
Indonesia is an archipelago with many traditional divers, however research on decompression sickness (DCS) has not yet elaborated. The aim of the study was to identify the prevalence of DCS and factors related to it. The study was conducted on October-November 2007 among fisherman moroami divers in Seribu Island Jakarta. Anamnesis and physical examination was taken before and three times after diving. Subject was diagnosed as having DCS if experienced one of these symptom or sign: myalgia, muscle pain, skin rash, ankle weakness, bowel movement & bladder dysfunction, visual disturbances, headache, vertigo, dyspnoe, chest pain, convulsion, unconsciousness, nausea and vomiting. Among 123 potential divers, five were having upper respiratory infection, so only 117 divers participated in this study. Final model analysis showed that regulator, valsava when having ear pain, ascending speed to surface, and lack of training were risk factors to obtain DCS. Divers whose ascending speed more than 9 m per minutes had two times risk to get DCS [adjusted ratio = 2.2; 95% confidence interval (CI)= 1.11 - 3.56]. Having DCS before diving, increased risk 20% (RRa = 1.20; 95% CI = 0.86-1.68; P=0,285). Beside knowledge to use regulator correctly and valsava, fisherman Moroami divers need to be trained to ascend speed to sea level surface less than 9 m per minute. (Med J Indones 2008; 17: 197-202)